Plano de Marketing para a Zani Fresh.co - Conceição, Ana Carolina Travizani Santos da (2022)
In the current scenario of constant evolution and transformation, the Marketing Plan is an essential tool for the organization to achieve its goals, developing more assertive marketing strategies that guarantee its competitive edge. The present work aims to develop a Marketing Plan for Zani Fresh.co, enabling a better understanding of its target audience, the market in which it is inserted and the definition of its objectives and strategies. In this way, descriptive research was carried out that had an online questionnaire where the data collected were treated quantitatively, to identify the profile of its customers and their preferences in the beachwear market. With the actions defined, the owner will bring improvements to the business and will follow the trends of this market.